Protective effect of carvedilol against anthracycline-induced cardiomyopathy on patients with breast cancer and lymphoma - Zamani, Bijan; R., Salehi; A., Esfahani (International Journal of Advances in Medicine, 2018)
Background:Anthracycline antibiotics are potent antineoplastic agents. Unfortunately, despite its broad effectiveness, anthracycline therapy is associated with irreversible dilated cardiomyopathy. Toxic effect may occur at any stage of anthracycline treatment. When it takes place, medical therapy is mostly insufficient. Therefore, prevention of cardiomyopathy has great clinical importance. This study aimed at evaluating the protective effect of carvedilol against anthracycline-induced cardiomyopathy on patients with breast cancer and lymphoma. Methods: In a randomized clinical trial, 66 patients with breast cancer or lymphoma selected for chemotherapy in Tabriz city hospital. These patients randomized in three groups; the first group (control) received placebo; the second group (A) received carvedilol 6.25mg/d and the third group (B) received carvedilol 12.5mg/d for 4months. Conventional echocardiography and tissue Doppler study were employed for evaluating the patients on the baseline and at the end of survey. Results:At the end of 4 months of follow-up, 1 (4.5%) patient in group B, 2 (9.1%) patients in group A and 4 (18.2%) patients of the control group had died. Clinical systolic dysfunction was encountered in 5 (27.8%), 5 (25%) and 1 (4.8%) patients in the control, A and B groups, respectively. A distinctive clinical diastolic dysfunction was encountered in 5 (27.8%), 3 (15%) and 3 (14.3%) patients in the control, A and B groups, respectively. Carvedilol with a dose of 6.25mg/d prohibited the diastolic dysfunction at the end of study without a significant effect on the prevention of diastolic dysfunction. Carvedilol with a dose of 12.5mg/d effectively prevented both the systolic and diastolic dysfunctions at the end of study. Conclusions:The current study showed that prophylactic administration of carvedilol with a dose of 12.5 mg/d might significantly prevent the systolic and diastolic dysfunction of the left ventricle in patients receiving chemotherapy with anthracycline.